KEBIJAKAN IMIGRASI ZAMAN HINDIA BELANDA (1913-1942) - Mundzir, Chaerul; Arif, Muhammad; Aksa, Aksa (Rihlah: Jurnal Sejarah dan Kebudayaan, 2021)
Abstract This paper describes the immigration that took place in the Dutch East Indies under the Dutch colonial rule. The immigration policy had applied in the Dutch East Indies which was called Open deur politiek or open door politics. Open Door Politics namely the policy that opened the Dutch East Indies as wide as possible for foreigners to enter permanently and become resident of the Netherlands Indies. The history of immigration in Indonesia began in 1913, since the Dutch East Indies government began implementing a colonial immigration law system. At that time there was a colonial government body called Immigratie Dienst which was in charge of handling immigration issues for the entire Dutch East Indies region. Keywords: Immigration; Open deur politiek; Dutch-Indies Abstrak Tulisan ini menjelaskan tentang imigrasi yang berlangsung di Hindia Belanda dibawah jajahan pemerintahan Belanda. Politik kebijakan keimigrasian yang diterapkan di Hindia-Belanda disebut opendeurpolitiek atau politik pintu terbuka yaitu kebijakan yang membuka wilayah Hindia-Belanda untuk seluas-luasnya bagi orang asing dapat masuk menetap dan menjadi penduduk Hindia-Belanda. Sejarah keimigrasian di Indonesia dimulai sejak tahun 1913, sejak pemerintah Hinda-Belanda mulai menjalankan ssstem hukum keimigrasian yang bersifat kolonial. Pada saat itu terdapat badan pemerintahan kolonial bernama Immigratie Dienst yang bertugas menangani masalah keimigrasian untuk seluruh kawasan Hindia-Belanda.